2020
DOI: 10.2174/1874210602014010717
|View full text |Cite
|
Sign up to set email alerts
|

Insights on Using Social Media in Dental Education: A Cross-Sectional Study in Saudi Arabia

Abstract: Objective: The purpose of this study is to investigate the insight of utilizing social media as an educational tool among dental faculty members in Saudi Arabia. Methods: A descriptive cross-sectional survey was distributed to 380 randomly selected faculty members from three governmental universities in the Western region of Saudi Arabia. The participants completed a validated questionnaire to assess the intent of usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…3,18 The final perceived risk factor was related to the time spent on DSM and is supported by existing literature. 38,39 With regard to the validity and reliability of the extracted factors, each factor was represented by items loading ≥0.5, which confirmed their validity. 20 Cronbach's alpha values ranged from 0.6 to 0.8, which supported the reliability of the factors.…”
Section: Cronbach's Alpha (α)mentioning
confidence: 54%
“…3,18 The final perceived risk factor was related to the time spent on DSM and is supported by existing literature. 38,39 With regard to the validity and reliability of the extracted factors, each factor was represented by items loading ≥0.5, which confirmed their validity. 20 Cronbach's alpha values ranged from 0.6 to 0.8, which supported the reliability of the factors.…”
Section: Cronbach's Alpha (α)mentioning
confidence: 54%
“…These findings correspond with a study in the literature that states the benefits of social media such as improving communication and sharing ideas and knowledge. 16 In our study, dentists did prefer using social media to buy and/or sell dental equipment. These findings have also been concluded in a study by Gadish et al where dental offices have been reported to switch to online purchasing of dental supplies and equipment.…”
Section: Discussionmentioning
confidence: 76%
“…The negative remarks on the videos were mostly addressed to further improve the quality and to use accurate and relevant keywords for search of the video [ 22 , 25 ], whereas the positive remarks mentioned about the quality of knowledge and information provided, clarity, and presentation skills [ 22 , 25 ]. Recently, due to the pandemic, there has been a shift towards digital learning and increased use of the internet and specifically YouTube to acquire knowledge and learn skills [ 13 , 22 ]. The goal of delivering knowledge online is attainable, given that all the dental professionals and specialists make efforts to provide improved quality content and information for the students [ 13 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, due to the pandemic, there has been a shift towards digital learning and increased use of the internet and specifically YouTube to acquire knowledge and learn skills [ 13 , 22 ]. The goal of delivering knowledge online is attainable, given that all the dental professionals and specialists make efforts to provide improved quality content and information for the students [ 13 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation